438 Is Cerebrospinal Fluid Sampling Necessary at The Time of First Ventriculo-Peritoneal Shunt Insertion in Paediatric Patients?. (4th May 2021) - Chia, C W L; Leach, P
Abstract: We aim to evaluate whether intraoperative cerebrospinal fluid (CSF) sampling during ventriculo-peritoneal (VP) shunt insertion can predict future shunt infection or guide its management, as there is currently no evidence for this. 83 paediatric patients undergoing VP shunt insertion between February 2013 and July 2019 were retrospectively identified. Patient demographics, presence of pre-operative extra ventricular drain (EVD), pre-operative CSF results, and intra-operative CSF results were identified. All patients were followed up for a minimum of 6 months for identification of shunt infection. 90 VP shunt insertions were performed in 83 patients. Age at time of shunt insertion ranged from 5 days to 15.8 years (mean 44.2 months). Tumours were the most common aetiology for hydrocephalus (n = 24). 67 cases (74.4%) had intra-operative CSF samples, of which 2 revealed the presence of bacteria. Only 1 patient with intraoperative CSF sampling positive for growth developed shunt infection during follow up. Two cases developed a shunt infection despite normal intra-operative CSF results. Three cases did not have intra-operative CSF sampling but developed a shunt infection during follow up. Our results show that intraoperative CSF sampling as a method to predict future risk of shunt infection and to help inform future antibiotic prescribing is unreliable.